High tumoral PD-L1 expression and low PD-1+ or CD8+ tumor-infiltrating lymphocytes are predictive of a poor prognosis in primary diffuse large B-cell lymphoma of the central nervous system. (2nd September 2019) - Kim, Sehui; Nam, Soo Jeong; Park, Changhee; Kwon, Dohee; Yim, Jeemin; Song, Seung Geun; Ock, Chan-Young; Kim, Young A; Park, Sung Hye; Kim, Tae Min; Jeon, Yoon Kyung
ABSTRACT: We investigated the clinicopathological role of the PD-1/PD-L1 pathway in primary diffuse large B-cell lymphoma of the central nervous system (PCNS-DLBCL) arising in the immune-privileged site. PD-L1 immunostaining of ≥30% of tumor cells was defined as tPD-L1+, and PD-L1 immunostaining of ≥30% of total cellularity, including tumor and non-tumoral cells, as tmPD-L1+ . PD-1 + and CD8 + tumor-infiltrating lymphocytes (TILs) were enumerated. Thirty-five cases (35.7%) were tPD-L1+ and 47 cases (48%) were tmPD-L1+ . The number of TILs was greater in tmPD-L1+ cases than in tmPD-L1− cases (CD8 +, P = .050; PD-1 +, P = .019). tPD-L1+ and tmPD-L1+ cases tended to have a poor performance status. In contrast, the numbers of CD8 + and PD-1 + TILs tended to be higher in patients with a good performance status and MYC/BCL2 negativity. Patients with tPD-L1+ had a worse overall survival ( P = .026), and those with increased CD8 + or PD-1 + TILs tended to have a better overall survival ( P = .081 and 0.044, respectively). Tumoral PD-L1 expression and the number of PD-1 + TILs were independent prognostic factors. tPD-L1+ patients with a small number of CD8 + or PD-1 + TILs had the worst prognosis, and tPD-L1− patients with a large number of CD8 + or PD-1 + TILs had the best prognosis. In validation group, increased CD8 + or PD-1 + TILs were significantly associated with a prolonged survival, but PD-L1 had no prognostic significance. In conclusion, PD-L1 is frequently expressed in tumor cells and the immune microenvironment of PCNS-DLBCL and is correlated with increased TILs. PD-L1 and CD8 + and PD-1 + TILs have potential as prognostic biomarkers and therapeutic targets in PCNS-DLBCL.